Students' mathematical reflective thinking ability on statistics material with STEAM approach - Machromah, Isnaeni Umi; Musthofa, Wafa Sandwi (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
Background: The STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in education has been gaining traction for its holistic and integrated framework that fosters critical and reflective thinking. Previous studies have shown its effectiveness in various aspects of mathematical competencies, yet there is limited research concerning its impact on students' reflective thinking skills in statistical material.Aim: This study aims to analyze students' mathematical reflective thinking skills in statistical material, using the STEAM approach.Method: Utilizing a qualitative research design, this study engaged six twelfth-grade students from MAN 1 Karanganyar as its subjects. Data were gathered through a combination of essay-based tests focused on data interpretation tasks and comprehensive interviews. The analysis was performed through observation, interviews, testing, and data triangulation, followed by thematic data reduction.Result: The findings disclose that students exhibited varying degrees of mastery over reflective thinking in the context of tackling statistical problems. While they demonstrated competence in technical and mathematical aspects under the STEAM approach, their proficiencies were less apparent in scientific, artistic, and technological dimensions.Conclusion: The study concludes that although the STEAM approach facilitates technical and mathematical skill enhancement, it may not fully equip students with comprehensive reflective thinking skills, particularly in statistical contexts. Therefore, there is a need for a more targeted pedagogical approach to bridge these gaps and cultivate well-rounded, reflective thinkers.